Optimization and characterization of rhamnolipids produced by Pseudomonas aeruginosa ATCC 9027 using molasses as a substrate - Braz, Letícia Martini; Salazar-Bryam, Ana María [UNESP]; Andrade, Grazielle Santos Silva; Tambourgi, Elias Basille (Springer Nature, 2023)
The present study aims to evaluate the growth potential of the P. aeruginosa ATCC9027 strain with molasses as the sole carbon source to produce rhamnolipids. The influence of the cultivation time and substrate concentration on biosurfactant production was investigated by using a complete 3-level factorial design, with the rhamnolipid concentration as the variable response. The strain was able to produce the biosurfactant in all design conditions tested, producing 758.04 mg/L rhamnolipids with 7% v/v substrate concentration in a cultivation time of 120 h. The substrate concentration used in the cultivation step directly influenced the biosurfactant production, and, even with the decrease in biomass growth, the biosurfactant production continued to increase. High Performance Liquid Chromatography (HPLC) revealed the presence of 62.3% mono- (RL1) and 37.6% di-rhamnolipids (RL3). The stability tests showed that the biosurfactant has good performance in extreme conditions of temperature, pH and saline concentration. The emulsification index was also evaluated for several oils and hydrocarbons, obtaining emulsification rates of up to 84.9% for the burnt motor oil. In addition, rhamnolipid showed a good ability to remove spilled oil from the sand, removing 58.51% of burnt motor oil and 70.09% of post-frying soybean oil. The results indicate that molasses, an agro-industrial residue abundant in Brazil, can be used as the only carbon source for quality rhamnolipid production when under optimized conditions, therefore presenting itself as a management option for this residue and, at the same time, providing the production product with high added value. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Agro-industrial subproduct; Biosurfactant; Molasses; Pseudomonas aeruginosa; Rhamnolipids